Analysis and processing of articulation tests data - Архипов, Александр Евгеньевич; Архипова, Елена Александровна (Ukrainian Information Security Research Journal, 2012)
The paper considers the question of expert evaluation results processing of verbal clarity for Ukrainian language during articulation tests that imitate recognition of speech message in the conditions of speech signal masking by acoustic hindrance. It is taken diagram of verbal clarity and the signal/noise ratio that can be used for solving the problems of speech information protection. It is confirmed that colored noise is more efficient than white noise. It is offered a descriptive model that at quality level allows to explain the process of errors forming of audio image (speech fragment + masking noise) perception by the auditor, explain the differences in articulation test results of colored and white noise masking, distribution features of intelligibility evaluation error at the different levels of masking hindrance.